The Relationship Between Union Commitment and Gender: Some Qualifying Factors - Thornthwaite, Louise (Relations industrielles / Industrial Relations, 1993)
During the early 1980s, equal opportunity officials were appointed within the management hierarchies of most New South Wales (NSW) government organizations. A study investigated women's choices of representation for discrimination grievances during the 1980s. Findings are based on preliminary research only, but they strongly suggest that equity officials within NSW government organizations may constitute a challenge to unions for the loyalties of women workers. They have emerged both as promoters of women's specific concerns and as a source of advice, assistance, and the formal means through which women can remedy grievances of an ostensibly individual nature on a range of employment issues. Also equity officials commonly administer an ad hoc, individualized grievance process which largely excludes trade unions and which competes directly with the collective mechanisms and representation offered by unions. Findings suggest that for women's and men's relative union commitment levels to be adequately assessed, factors other than union-related attitudinal dimensions also require consideration.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Grievances; Labor Unions; Organizational behavior; Public sector; Sex discrimination; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies; Women